Analisis Kesulitan Matematika Materi Jarak dan Kecepatan pada Siswa Kelas Tinggi SD Kutajaya 1 - Humaerah, Humaerah; Afrilia, Nanda Nurul; Zhalila, Zhillan (Lembaga Yasin AlSys, 2022)
Education is an important thing in shaping the character and intelligence of the nation's children where formal education is divided into elementary, middle, high school, to tertiary schools, at the level of every learning carried out must be well conceptualized and adapted to the character of students, especially at the elementary level. where all basic lessons will be taught and will be a provision to continue further education, especially learning mathematics that is assessed, therefore a good concept is needed. One of the materials in elementary school is distance, time, and speed, this becomes a particular difficulty. The study was conducted to analyze how the difficulty of learning mathematics with distance, time and speed materials for elementary school students 5 SD Negeri Kutajaya 1, this study used a qualitative descriptive method by conducting direct analysis and interviews where grade 5 students at SD Negeri Kutajaya 1 experienced problems in learning. mathematics with material distance, time, and speed. It is proven by several errors and the final score is not in accordance with the specified KKM.